The Implementation of the Independent Learning Curriculum in Islamic Religious Education for Grade V at SD Negeri Lempuyangwangi Yogyakarta: Penerapan Kurikulum Merdeka Belajar Pada Pembelajaran PAI Kelas V Di SD Negeri Lempuyangwangi Yogyakarta - Fatimah Jahroh; Viva Fadma Onilivia; Sabarudin; Rizqi Lestari (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to implement the Merdeka Belajar Curriculum in Islamic Religious Education (PAI) learning in grade V of Lempuyangwangi State Elementary School, Yogyakarta. The Merdeka Belajar Curriculum is implemented as a solution to the learning crisis due to the COVID-19 pandemic and to answer the needs of education in the digital era. This study uses a qualitative approach with in-depth interview and observation methods, involving PAI teachers as the main subjects of the study. The results of the study indicate that the implementation of the Merdeka Belajar Curriculum in Lempuyangwangi State Elementary School has been carried out in stages, starting from grades I and IV, with intensive training for teachers to understand curriculum concepts, prepare learning tools, and implement the Pancasila Student Profile Strengthening Project (P5). This curriculum has a positive impact, such as increasing student involvement in more relevant, interactive, and project-based learning, as well as facilitating the exploration of student interests and talents. However, there are significant challenges in its implementation, such as limited facilities, time preparation, and a learning paradigm that must shift from being teacher-focused to student-focused. To overcome these challenges, the school provides ongoing training, additional learning resources, and collaboration between teachers. This study confirms that the Independent Learning Curriculum has great potential in creating a learning atmosphere that is more independent, innovative, and in accordance with today's educational needs.